Prevalencia de violencia de género en mujeres, en el cantón Calvas - Rodríguez Romero, Daniela Mishell (2023)
Gender violence, being a persistent and serious problem at a global level, demands a deep understanding and concrete actions to address it. In this context, a quantitative, descriptive and transversal research was carried out in the Calvas Canton during 2021, with the purpose of analyzing the prevalence of gender violence in women and contributing to the baseline of the project "Asymmetry of Power in the Calvas Canton" of the National University of Loja. The methodology used included the application of 232 surveys, using a quantitative approach that allowed the affected women to be demographically characterized. The results revealed that the majority of the affected women were between 36 and 55 years old, the majority in a common law union, with a secondary education level, unemployed and housewives, without affiliation to the Ecuadorian Social Security Institute. The prevalence of violence was 58% in the women of Calvas, with verbal violence identified as a significant component, negatively affecting the women's selfesteem and presenting challenges to exit the cycle of abuse. Furthermore, the under-detection of the problem was highlighted, indicating possible limitations associated with the quantitative nature of the study and the stigma linked to gender violence. In conclusion, the need to strengthen comprehensive care for victims was highlighted, focusing on raising awareness about support resources and the implementation of protocols to avoid revictimization. The importance of addressing gender inequalities and abuse of power to promote equity and protect the health of women in Canton Calvas was emphasized.